Spatial-Memory Formation After Spaced Learning Involves ERKs1/2 Activation Through a Behavioral-Tagging Process - Tintorelli, Ramiro Gastón (2020)
The superiority of spaced over massed learning is an established fact in the formation of long-term memories (LTM). Here we addressed the cellular processes and the temporal demands of this phenomenon using a weak spatial object recognition (wSOR) training, which induces short-term memories (STM) but not LTM. We observed SOR-LTM promotion when two identical wSOR training sessions were spaced by an inter-trial interval (ITI) ranging from 15 min to 7 h, consistently with spaced training. The promoting effect was dependent on neural activity, protein synthesis and ERKs1/2 activity in the hippocampus. Based on the “behavioral tagging” hypothesis, which postulates that learning induces a neural tag that requires proteins to induce LTM formation, we propose that retraining will mainly retag the sites initially labeled by the prior training. Thus, when weak, consecutive training sessions are experienced within an appropriate spacing, the intracellular mechanisms triggered by each session would add, thereby reaching the threshold for protein synthesis required for memory consolidation. Our results suggest in addition that ERKs1/2 kinases play a dual role in SOR-LTM formation after spaced learning, both inducing protein synthesis and setting the SOR learning-tag. Overall, our findings bring new light to the mechanisms underlying the promoting effect of spaced trials on LTM formation.